ANALYSIS OF THE EFFECT OF E-CRM AUTOMATION ON SERVICE EFFICIENCY AT DIAH FASHION STORE - Dinda Elpita Sari Munthe; Fauriatun Helmiah; Chitra Latiffani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: The rapid development of digital technology has brought significant changes in consumption patterns and customer behavior, particularly in the fashion retail sector. Increasing competition and rising cynsumer expectations for fast, accurate, and technology-based services require businesses to innovate and undergo digital transformation. One widely used approach is the implementation of automation-based Electronic Customer Relationship Management (E-CRM). This study aims to analyze the implementation of E-CRM automation and its impact on service efficiency at Toko Diah Fashion, a fashion retail business that still faces service challenges due to manual systems, such as customer data duplication, delayed responses, and difficulty in monitoring transaction history. The research method used is a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research focus is limited to aspects of service efficiency, including service speed, accuracy in managing customer data, and ease in customer follow-up. The E-CRM automation system studied is designed using PHP programming language and a MySQL database. The research results indicate that the implementation of E-CRM automation can significantly improve service efficiency. This system facilitates integrated customer data management, speeds up the service process, and supports more personalized communication through notification features and transaction history recording. Keyword: automation; e-crm; fashion retail; service efficiency. Abstrak: Perkembangan teknologi digital yang semakin pesat telah membawa perubahan signifikan dalam pola konsumsi dan perilaku pelanggan, khususnya dalam sektor ritel fashion. Persaingan yang semakin ketat serta meningkatnya ekspektasi konsumen terhadap layanan yang cepat, akurat dan berbasis teknologi menuntut pelaku usaha untuk melakukan inovasi dan transformasi digital. Salah satu pendekatan yang banyak digunakan adalah penerapan Electronic Customer Relationship Management (E-CRM) berbasis automasi. Penelitian ini bertujuan untuk menganalisis penerapan automasi E-CRM serta pengaruhnya terhadap efisiensi pelayanan pada Toko Diah Fashion, sebuah usaha ritel fashion yang masih menghadapi kendala pelayanan akibat sistem manual, seperti duplikasi data pelanggan, keterlambatan respons, dan kesulitan dalam pemantauan histori transaksi. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Fokus penelitian dibatasi pada aspek efisiensi pelayanan, meliputi kecepatan pelayanan, ketepatan pengelolaan data pelanggan, serta kemudahan dalam tindak lanjut pelanggan. Sistem automasi E-CRM yang dikaji dirancang menggunakan bahasa pemrograman PHP dan basis data MySQL. Hasil penelitian menunjukkan bahwa penerapan automasi E-CRM mampu meningkatkan efisiensi pelayanan secara signifikan. Sistem ini mempermudah pengelolaan data pelanggan secara terintegrasi, mempercepat proses pelayanan, serta mendukung komunikasi yang lebih personal melalui fitur notifikasi dan pencatatan histori transaksi. Kata kunci: automasi; e-crm; efisiensi pelayanan; ritel fashion.